2017
DOI: 10.7752/jpes.2017.02091
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The goal of the article is to discuss the pressing concern and to improve the quality of physical training of future law enforcement and police officers. Statistics show a significant increase in the rate of attacks, including gunmen and criminal attacks, on law enforcement agencies. Moreover, police officers and other Special Forces units should have the perfect fighting combat manoeuvres and skills to protect themselves from silent and automatic weapons to have a successful response to armed criminals. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…An analysis of the level of technical preparedness of Russian police officers for the successful counteraction to armed criminals has shown that there is a clear separation in the training programs for police officers for shock and throwing equipment with a clear predominance of percussion techniques in the performance of combat techniques. This is because most specialists training police officers themselves specialized in various types of shock martial arts (Osipov, Kudryavtsev, Galimova, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the level of technical preparedness of Russian police officers for the successful counteraction to armed criminals has shown that there is a clear separation in the training programs for police officers for shock and throwing equipment with a clear predominance of percussion techniques in the performance of combat techniques. This is because most specialists training police officers themselves specialized in various types of shock martial arts (Osipov, Kudryavtsev, Galimova, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…There are many problems impeding the way of sports perfection of athletes specializing in combat sambo. For example, the imperfection of the current training program for officers and employees in the law enforcement agencies of the Russian Federation is described as a fascination with striking action in the rack and inadequate possession of effective protection methods lying on the ground (Osipov, Kudryavtsev, Galimova, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…www.efsupit.ro 590 curriculum for cadets and officers currently practicing in the educational institutions of the Ministry of the Internal Affairs of Russia for the implementation of combat methods of the combat consists of training in kick activities in the rack (Osipov, Kudryavtsev, Galimova, et al, 2017). This is done to increase the level of special preparedness of the servicemen of law enforcement agencies and special units to confront offenders and criminals actively who are often armed.…”
Section: Discussionmentioning
confidence: 99%